2005
DOI: 10.1016/j.bbamcr.2004.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of hyaluronan in cultured rabbit growth plate chondrocytes during differentiation

Abstract: Hyaluronan (HA) is one of the major extracellular matrix components in cartilage. In addition to the biomechanical functions, HA has various important roles in the differentiation of chondrocytes. The purpose of this study was to clarify the nature of HA synthesis during chondrocyte differentiation. Growth plate chondrocytes were isolated from rabbit ribs and cultured in chondrocyte differentiation medium. The amount of HA and HA synthase (HAS) mRNA levels were analyzed for each stage of chondrocyte differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In the present study, we have shown that Has2 expression is strongly upregulated at the onset of hypertrophic maturation in normal skeletal elements during the conversion of immature proliferating chondrocytes into postmitotic prehypertrophic chondrocytes, a critical step in the maturation process. Others have also shown that Has2 is the major HA synthase expressed in growth plate chondrocytes at the onset of hypertrophic maturation (Takeda et al, 1999;Suzuki et al, 2005;Schmidl et al, 2006). Moreover, we have confirmed the observations of others that hypertrophying chondrocytes are surrounded by HA-rich pericellular coats in which HA is bound to its receptor, CD44 (Knudson, 1993;Pavasant et al, 1996;Shibata et al, 2003;Knudson and Knudson, 2004;Suzuki et al, 2005).…”
Section: Development Developmentsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, we have shown that Has2 expression is strongly upregulated at the onset of hypertrophic maturation in normal skeletal elements during the conversion of immature proliferating chondrocytes into postmitotic prehypertrophic chondrocytes, a critical step in the maturation process. Others have also shown that Has2 is the major HA synthase expressed in growth plate chondrocytes at the onset of hypertrophic maturation (Takeda et al, 1999;Suzuki et al, 2005;Schmidl et al, 2006). Moreover, we have confirmed the observations of others that hypertrophying chondrocytes are surrounded by HA-rich pericellular coats in which HA is bound to its receptor, CD44 (Knudson, 1993;Pavasant et al, 1996;Shibata et al, 2003;Knudson and Knudson, 2004;Suzuki et al, 2005).…”
Section: Development Developmentsupporting
confidence: 78%
“…Others have also shown that Has2 is the major HA synthase expressed in growth plate chondrocytes at the onset of hypertrophic maturation (Takeda et al, 1999;Suzuki et al, 2005;Schmidl et al, 2006). Moreover, we have confirmed the observations of others that hypertrophying chondrocytes are surrounded by HA-rich pericellular coats in which HA is bound to its receptor, CD44 (Knudson, 1993;Pavasant et al, 1996;Shibata et al, 2003;Knudson and Knudson, 2004;Suzuki et al, 2005). It has been suggested that the HA-rich pericellular coats may exert a swelling pressure that might aid in the expansion of the growth plate (Pavasant et al, 1996).…”
Section: Development Developmentmentioning
confidence: 99%
“…Electron microscopy studies have shown that aggrecan aggregates in the hypertrophic zone are smaller than in other zones, due to a decrease in the length of HA to which aggrecan is bound [106,107]. Other studies show that HA released from rabbit growth plate chondrocytes during in vitro differentiation has a broad ranging 404 E. R. Bastow et al Synthesis and degradation of hyaluronan molecular mass [226]. Since hyal1 and hyal2 are expressed in the proliferative and hypertrophic zones of rabbit growth plate [227], these results suggest that HYALs, and synthases producing high M r HA, are active concurrently.…”
Section: Hyals and Hass In Longitudinal Bone Growthmentioning
confidence: 94%
“…Conversely, aberrant HA production could lead to abnormal or insufficient hypertrophic expansion and might contribute to the phenotype in some skeletal dysplasias [223]. It is not clear which synthases produce HA in human hypertrophic chondrocytes; however, has2 and has3 mRNAs are maximally expressed in prehypertrophic rabbit growth plate chondrocytes [226] and has1-3 are detected by in situ hybridisation in hypertrophic chondrocytes of mouse growth plate [91]. The growth plate is highly dynamic; within each zone there is extensive remodelling and it appears that in the hypertrophic zone, HA production and degradation proceed simultaneously.…”
Section: Hyals and Hass In Longitudinal Bone Growthmentioning
confidence: 99%
“…Previous work has demonstrated that hyaluronan produced by Has2 is essential for normal growth plate chondrocyte hypertrophy (Alini et al, 1992;Pavasant et al, 1996;Suzuki et al, 2005). Thus, normal chondrocyte differentiation and hypertrophy in fetal bone development and that in juvenile growth both rely upon Has2-mediated hyaluronan production to organize an appropriate extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%